Analysis of the bridge failure direction and the increased probability of collapse due to multi-hazard effects: scour and earthquakes - Bertha A. Olmos; Jose M. Jara; Alberto Gil; Juan I. López-Pérez; Guillermo Martínez; Alma R. Sánchez (Bulletin of Earthquake Engineering, 2026)

The role of melatonin timing on short-term memory retention during sleep restriction - Karyme M. Alemán-Villa; Hugo J. Sosa-Arámbula; David A. Armienta-Rojas; Josué Camberos-Barraza; Ángel R. Rábago-Monzón; Alejandro Camacho-Zamora; Juan F. Osuna-Ramos; Javier A. Magaña-Gómez; Alma M. Guadrón-Llanos; Loranda Calderón-Zamora; Claudia D. Norzagaray-Valenzuela; Marco A. Valdez-Flores; et al. (Psychopharmacology, 2026)

Taxon-specific responses to temperature, landscape, and local management challenge common strategies for pest control in vineyards - Costanza Geppert; Alberto Alma; Lucia Andretta; Gianfranco Anfora; Enrico Busato; Pierfilippo Cerretti; Serena Giorgia Chiesa; Arturo Cocco; Elena Costi; Mariana da Cruz Albertazzi; Carlo Duso; Pierluigi Forlano; et al. (Agriculture, Ecosystems & Environment, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Assessment of symbiont-targeted control on non-target stink bugs and their associated egg parasitoids: Could this technique be suitable against Halyomorpha halys in New Zealand? - Sofia V. Prieto; Gonzalo A. Avila; Barbara Lima; Elena Gonella; Alberto Alma (Journal of Pest Science, 2025)
The potential arrival of Halyomorpha halys in New Zealand jeopardizes a vast range of crops. Therefore, different preparedness strategies are being assessed before its arrival. A symbiont-targeted control strategy might be used along with other control tactics such as biological control. Prior its implementation, it is necessary to assess its potential impact on non-target stink bug species and their associated egg parasitoids. In this study, the effect of symbiont-targeted control was evaluated on three stink bug species in New Zealand, Oechalia schellenbergii (a native predatory species), Nezara viridula (a cosmopolitan pest) and Monteithiella humeralis (a non-pest adventive species). The interference of anti-symbiont treatment of egg masses with their associated Trissolcus egg parasitoids, namely T. basalis and T. oenone , was also tested. A variable response to symbiont elimination was observed in stink bug species, with N. viridula and M. humeralis undergoing high mortality and no negative effect detected for O. schellenbergii . Parasitism of N. viridula by T. basalis declined on egg masses treated with an anti-symbiont biocomplex or water. Similar results were obtained for T. oenone parasitizing eggs of M. humeralis ; while, a parasitism increase was observed for O. schellenbergii egg masses exposed to anti-symbiont treatment and treated with water. These results confirm previous evidence of species-specific response to anti-symbiont control and indicate a moderate and variable effect on egg parasitism. Such responses suggest that symbiont-targeted control would not significantly interfere with the native insect communities that may interact with H. halys , encouraging the future incorporation of symbiont-targeted control in pest management programs.

Field evaluation of symbiont-targeted control of Halyomorpha halys in hazelnut crop - Matteo Dho; Elena Gonella; Alberto Alma (Crop Protection, 2025)

Exploring the general chemistry of the core and ocean of Enceladus - Alma Karen Ramírez-Cabañas; Alberto Flandes; Pedro Elías Mirón-Enríquez (Advances in Space Research, 2024)

Phytoplasma identification in pome fruit trees and Cacopsylla bidens (Hemiptera: Psyllidae) in Jordan - Asem Habes Abu Alloush; Piero Attilio Bianco; Alberto Alma; Rosemarie Tedeschi; Fabio Quaglino (European Journal of Plant Pathology, 2024)

Climate and landscape composition explain agronomic practices, pesticide use and grape yield in vineyards across Italy - Costanza Geppert; Mariana da Cruz; Alberto Alma; Lucia Andretta; Gianfranco Anfora; Donatella Battaglia; Giovanni Burgio; Vittoria Caccavo; Serena Giorgia Chiesa; Francesca Cinquatti; Arturo Cocco; Elena Costi; et al. (Agricultural Systems, 2024)

Protective and curative effect of an experimental biocomplex against Flavescence dorée phytoplasma infection and transmission by Scaphoideus titanus under laboratory conditions - Elena Gonella; Andrea Arpellino; Luca Picciau; Federico Lessio; Marco Prati; Luca Bucci; Matteo Dho; Alberto Alma (Crop Protection, 2024)

The applications of CRISPR/Cas-mediated microRNA and lncRNA editing in plant biology: shaping the future of plant non-coding RNA research - Luis Alberto Bravo-Vázquez; Andrea Méndez-García; Verenice Chamu-García; Alma L. Rodríguez; Anindya Bandyopadhyay; Sujay Paul (Planta, 2024)

Morphological characterization of the antenna of Torymus sinensis (Hymenoptera: Torymidae) and a comparison within the superfamily Chalcidoidea - Marco Pezzi; Cristina Munari; Michele Mistri; Chiara Scapoli; Milvia Chicca; Marilena Leis; Carmen Scieuzo; Antonio Franco; Rosanna Salvia; Chiara Ferracini; Alberto Alma; Patrizia Falabella; et al. (Arthropod Structure & Development, 2024)

The controlled incineration process as an alternative to handle MSW and generate electric energy in the state of Guanajuato, Mexico - Carlos Alberto Rubio-Jimenez; Cristina Ramirez-Olmos; Alma Cecilia Lopez-Perez; Ana Lucia Perez-Pantoja; Gabriela Ana Zanor; Jose de Jesus Nezahualcoyotl Segoviano-Garfias (Energy and Climate Change, 2023)

No adverse effects of symbiotic control on the parasitism of Halyomorpha halys by egg parasitoids - Bianca Orrù; Silvia T. Moraglio; Francesco Tortorici; Elena Gonella; Luciana Tavella; Alberto Alma (Journal of Pest Science, 2023)
The brown marmorated stink bug Halyomorpha halys is a polyphagous insect, which has a devastating impact on agricultural production in many countries. The alteration of symbiont vertical transmission, by removing symbionts from stink bug eggs (symbiotic control), has been recently introduced in control programmes against this insect. A major advantage of this strategy is the compatibility with natural enemies, since it allows an insecticide-free approach that is not harmful to other agroecosystem components. However, the effect of anti-symbiont products on parasitism by egg parasitoids is still unexplored. Here, we investigated the impact on parasitism by native ( Anastatus bifasciatus , Ooencyrtus telenomicida and Trissolcus kozlovi ) and exotic ( Trissolcus japonicus and Trissolcus mitsukurii ) parasitoids that attack H. halys eggs, after treatment with the micronutrient biocomplex Dentamet ® , used for symbiotic control. The native wasp species were tested in no-choice bioassays, showing that treatment of the egg masses did not affect emergence percentages, but the non-reproductive effects were often reduced by the biocomplex. The exotic species T. japonicus and T. mitsukurii were used in no-choice and paired choice bioassays, showing an opposite influence of Dentamet ® on emergence percentage and preference in the two species. No-choice tests indicated the highest successful parasitoid emergence on biocomplex-treated egg masses for T. japonicus , while no preference in the paired comparison with eggs treated with water or untreated. In contrast, T. mitsukurii displayed the lowest parasitism after Dentamet ® treatment in no-choice tests, and preferred egg masses without Dentamet ® in paired choice tests. We did not record any natural symbiont acquisition by the parasitoids emerged from H. halys egg masses, indicating that the wasp fitness is very unlikely to be altered by dysbiotic effects resulting from treatments. Therefore, our results support a further implementation of symbiotic control in different crops in combination with biological control, as sustainable options for H. halys integrated pest management.

Association of seven ‘Candidatus Phytoplasma’ species to an almond disease complex in Jordan, and preliminary information on their putative insect vectors - Asem Habes Abu Alloush; Piero Attilio Bianco; Enrico Busato; Amre AlMahasneh; Alberto Alma; Rosemarie Tedeschi; Fabio Quaglino (Crop Protection, 2023)

Shifts in the seasonal trophic ecology of larvae and juveniles of European hake ( Merluccius merluccius ): From the Galician upwelling system (NW Spain) - Raúl Laiz‐Carrión; Águeda Cabrero; José María Quintanilla; Alma Hernández; Amaya Uriarte; Jesús Gago; José María Rodríguez; Carmen Piñeiro; Alberto García; Fran Saborido‐Rey (Fisheries Oceanography, 2022)
The trophic ecology of European hake ( Merluccius merluccius ) larvae and early‐juveniles from the Iberian shelf off Galicia (NW Spain) are assessed by means of stable isotopes (SIA) and nutritional condition in conjunction with hydrobiological variations observed during the winter and summer season of 2012. Hake early‐juveniles (18–47 mm SL) showed higher δ 15 N than larvae (3–11 mm SL) together with the microzooplankton (55–200 μm) and mesozooplankton (>200 μm) during both seasons. Low δ 15 N values and high variability in both zooplankton and hake larvae were found during winter coinciding with an unusually strong upwelling event. Inversely, high δ 15 N content in zooplankton in summer suggests strong nitrogen reutilization. However, hake larvae sampled in summer had a higher RNA:DNA ratio in line with higher Fulton condition factors than those sampled in winter. Higher δ 13 C values for microzooplankton and mesozooplankton and hake larvae in summer compared to late winter point to prey availability differences. The relationship between nitrogen and carbon stable isotopes versus size or weight suggests an ontogenetic shift in the diet of hake larvae. Early‐juveniles had a lower isotopic niche width compared to larvae in both late winter and summer, indicating a trophic specialization related to changes following settlement process from planktonic life to demersal habitat. Higher trophic specialization was observed in summer, which recorded a narrower isotopic niche and higher trophic position estimations.

Between uncertainty and hope: Young leaders as agents of change in sustainable small-scale fisheries - Alejandro Espinoza-Tenorio; Romana Gabriela Ehuan-Noh; Gabriela Alejandra Cuevas-Gómez; Nemer E. Narchi; Dora Elia Ramos-Muñoz; Francisco J. Fernández-Rivera Melo; Antonio Saldívar-Moreno; José Alberto Zepeda-Domínguez; Juan Carlos Pérez-Jiménez; Alma Oliveto-Andrade; Jorge Torre (Ambio, 2022)
The path to sustainable small-scale fisheries (SSF) is based on multiple learning processes that must transcend generational changes. To understand young leaders from communities with sustainable SSF management practices in Mexico, we used in-depth interviews to identify their shared motivations and perceptions for accepting their fishing heritage. These possible future decision-makers act as agents of change due to their organizational and technological abilities. However, young people are currently at a crossroads. Many inherited a passion for the sea and want to improve and diversify the fishing sector, yet young leaders do not want to accept a legacy of complicated socioenvironmental conditions that can limit their futures. These future leaders are especially concerned by the uncertainty caused by climate change. If fishing and generational change are not valued in planning processes, the continuity of fisheries, the success of conservation actions, and the lifestyles of young fishers will remain uncertain. Graphical abstract

Epidemiological surveillance of chikungunya fever in Mexico since its introduction in 2014–2016 and identification of circulating genotypes - Belem Torres-Longoria; David Esaú Fragoso-Fonseca; Alma Núñez-León; María de la Luz Torres; Mauricio Vázquez-Pichardo; Noé Escobar-Escamilla; Claudia Wong-Arámbula; José Ernesto Ramírez-González; Alfonso Méndez-Tenorio; María Eugenia Castro-Mussot; María M. B. Moreno-Altamirano; Jorge Membrillo-Hernández; et al. (Molecular Biology Reports, 2021)

Developmental stages and gut microenvironments influence gut microbiota dynamics in the invasive beetle Popillia japonica Newman (Coleoptera: Scarabaeidae) - Bessem Chouaia; Nizar Goda; Giuseppe Mazza; Sumer Alali; Fiorella Florian; Fabrizia Gionechetti; Matteo Callegari; Elena Gonella; Giulia Magoga; Marco Fusi; Elena Crotti; Daniele Daffonchio; et al. (Environmental Microbiology, 2019)
Summary Popillia japonica Newman (Coleoptera: Scarabaeidae) is a highly polyphagous invasive beetle originating from Japan. This insect is highly resilient and able to rapidly adapt to new vegetation. Insect‐associated microorganisms can play important roles in insect physiology, helping their hosts to adapt to changing conditions and potentially contributing to an insect's invasive potential. Such symbiotic bacteria can be part of a core microbiota that is stably transmitted throughout the host's life cycle or selectively recruited from the environment at each developmental stage. The aim of this study was to investigate the origin, stability and turnover of the bacterial communities associated with an invasive population of P. japonica from Italy. Our results demonstrate that soil microbes represent an important source of gut bacteria for P. japonica larvae, but as the insect develops, its gut microbiota richness and diversity decreased substantially, paralleled by changes in community composition. Notably, only 16.75% of the soil bacteria present in larvae are maintained until the adult stage. We further identified the micro‐environments of different gut sections as an important factor shaping microbiota composition in this species, likely due to differences in pH, oxygen availability and redox potential. In addition, P. japonica also harboured a stable bacterial community across all developmental stages, consisting of taxa well known for the degradation of plant material, namely the families Ruminococcacae, Christensenellaceae and Lachnospiraceae. Interestingly, the family Christensenallaceae had so far been observed exclusively in humans. However, the Christensenellaceae operational taxonomic units found in P. japonica belong to different taxonomic clades within this family.

Effectiveness of Torymus sinensis: a successful long-term control of the Asian chestnut gall wasp in Italy - Chiara Ferracini; Ester Ferrari; Marianna Pontini; Matteo A. Saladini; Alberto Alma (Journal of Pest Science, 2019)

Trophic ecology of European hake (Merlucius merlucius) larvae by stable isotopes analysis influenced by seasonal variability of oceanographic conditions off NW Galician waters. - Raul Carrion; Agueda Rodriguez; Jos M. Ervas; Alma De Rojas; Jose Maria Lopez; Piñeiro Carmen; Alberto Garcia (Frontiers in Marine Science, 2019)

Genetic variability among Mexican Mestizo and Amerindian populations based on three ABCB1 polymorphisms - Alma Faviola Favela-Mendoza; Héctor Rangel-Villalobos; Ingrid Fricke-Galindo; Alberto Ortega-Vázquez; Gabriela Martínez-Cortés; Marisol López-López (Molecular Biology Reports, 2018)

Asaia symbionts interfere with infection by Flavescence dorée phytoplasma in leafhoppers - Elena Gonella; Elena Crotti; Mauro Mandrioli; Daniele Daffonchio; Alberto Alma (Journal of Pest Science, 2018)

Post-release evaluation of non-target effects of Torymus sinensis, the biological control agent of Dryocosmus kuriphilus in Italy - Chiara Ferracini; Ester Ferrari; Marianna Pontini; Lindsay Karen Hernández Nova; Matteo A. Saladini; Alberto Alma (BioControl, 2017)

Olfactory attraction of Drosophila suzukii by symbiotic acetic acid bacteria - Fabio Mazzetto; Elena Gonella; Elena Crotti; Violetta Vacchini; Michail Syrpas; Marianna Pontini; Sven Mangelinckx; Daniele Daffonchio; Alberto Alma (Journal of Pest Science, 2016)

Identification of Asian genotype of chikungunya virus isolated in Mexico - José Alberto Díaz-Quiñonez; Noé Escobar-Escamilla; Joanna Ortíz-Alcántara; Mauricio Vázquez-Pichardo; María de la Luz Torres-Rodríguez; Alma Nuñez-León; Belem Torres-Longoria; Irma López-Martínez; Cuitláhuac Ruiz-Matus; Pablo Kuri-Morales; José Ernesto Ramírez-González (Virus Genes, 2016)

Non-target host risk assessment for the parasitoid Torymus sinensis - Chiara Ferracini; Ester Ferrari; Matteo Alessandro Saladini; Marianna Pontini; Marida Corradetti; Alberto Alma (BioControl, 2015)

Novel insight in the life cycle of Torymus sinensis, biocontrol agent of the chestnut gall wasp - Chiara Ferracini; Elena Gonella; Ester Ferrari; Matteo Alessandro Saladini; Luca Picciau; Federica Tota; Marianna Pontini; Alberto Alma (BioControl, 2015)

Environmental factors and agronomic practices associated with Savi’s pine vole abundance in Italian apple orchards - Sandro Bertolino; Laura Asteggiano; Matteo A. Saladini; Luca Giordani; Graziano Vittone; Alberto Alma (Journal of Pest Science, 2015)

Erratum to: Different mosquito species host Wickerhamomyces anomalus (Pichia anomala): perspectives on vector-borne diseases symbiotic control - Irene Ricci; Michela Mosca; Matteo Valzano; Claudia Damiani; Patrizia Scuppa; Paolo Rossi; Elena Crotti; Alessia Cappelli; Ulisse Ulissi; Aida Capone; Fulvio Esposito; Alberto Alma; et al. (Antonie van Leeuwenhoek, 2014)

Copper-mediated genotoxic stress is attenuated by the overexpression of the DNA repair gene MtTdp2α (tyrosyl-DNA phosphodiesterase 2) in Medicago truncatula plants - Matteo Faè; Alma Balestrazzi; Massimo Confalonieri; Mattia Donà; Anca Macovei; Alberto Valassi; Giorgio Giraffa; Daniela Carbonera (Plant Cell Reports, 2014)

Enhanced osmotic stress tolerance in Medicago truncatula plants overexpressing the DNA repair gene MtTdp2α (tyrosyl-DNA phosphodiesterase 2) - Massimo Confalonieri; Matteo Faè; Alma Balestrazzi; Mattia Donà; Anca Macovei; Alberto Valassi; Giorgio Giraffa; Daniela Carbonera (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Natural enemies of the South American moth, Tuta absoluta, in Europe, North Africa and Middle East, and their potential use in pest control strategies - Lucia Zappalà; Antonio Biondi; Alberto Alma; Ibrahim J. Al-Jboory; Judit Arnò; Ahmet Bayram; Anaïs Chailleux; Ashraf El-Arnaouty; Dan Gerling; Yamina Guenaoui; Liora Shaltiel-Harpaz; Gaetano Siscaro; et al. (Journal of Pest Science, 2013)

Incidence of ‘Candidatus Liberibacter europaeus’ and phytoplasmas in Cacopsylla species (Hemiptera: Psyllidae) and their host/shelter plants - Caterina Camerota; Noura Raddadi; Alan Pizzinat; Elena Gonella; Elena Crotti; Rosemarie Tedeschi; Netta Mozes-Daube; Ibolya Ember; Zoltan Acs; Maria Kolber; Einat Zchori-Fein; Daniele Daffonchio; et al. (Phytoparasitica, 2012)

Torymus sinensis: a viable management option for the biological control of Dryocosmus kuriphilus in Europe? - Melanie Gibbs; Karsten Schönrogge; Alberto Alma; George Melika; Ambra Quacchia; Graham N. Stone; Alexandre Aebi (BioControl, 2011)

The yeast Wickerhamomyces anomalus ( Pichia anomala ) inhabits the midgut and reproductive system of the Asian malaria vector Anopheles stephensi - Irene Ricci; Claudia Damiani; Patrizia Scuppa; Michela Mosca; Elena Crotti; Paolo Rossi; Aurora Rizzi; Aida Capone; Elena Gonella; Patrizia Ballarini; Bessem Chouaia; N' fale Sagnon; et al. (Environmental Microbiology, 2011)
Summary While symbiosis between bacteria and insects has been thoroughly investigated in the last two decades, investments on the study of yeasts associated with insects have been limited. Insect‐associated yeasts are placed on different branches of the phylogenetic tree of fungi, indicating that these associations evolved independently on several occasions. Isolation of yeasts is frequently reported from insect habitats, and in some cases yeasts have been detected in the insect gut and in other organs/tissues. Here we show that the yeast Wickerhamomyces anomalus , previously known as Pichia anomala , is stably associated with the mosquito Anopheles stephensi , a main vector of malaria in Asia. Wickerhamomyces anomalus colonized pre‐adult stages (larvae L 1 –L 4 and pupae) and adults of different sex and age and could be isolated in pure culture. By a combination of transmission electron microscopy and fluorescent in situ hybridization techniques, W. anomalus was shown to localize in the midgut and in both the male and female reproductive systems, suggesting multiple transmission patterns.

‘ Candidatus Liberibacter europaeus’ sp. nov. that is associated with and transmitted by the psyllid Cacopsylla pyri apparently behaves as an endophyte rather than a pathogen - Noura Raddadi; Elena Gonella; Caterina Camerota; Alan Pizzinat; Rosemarie Tedeschi; Elena Crotti; Mauro Mandrioli; Piero Attilio Bianco; Daniele Daffonchio; Alberto Alma (Environmental Microbiology, 2011)
Summary ‘ Candidatus Liberibacter spp.’ cause serious plant diseases. ‘ Candidatus Liberibacter asiaticus’, ‘ Ca. L. americanus’ and ‘ Ca. L. africanus’ are the aetiological agents of citrus greening (Huanglongbing) in Asia, America and Africa. ‘ Candidatus Liberibacter solanacearum’ causes diseases in Solanaceae in America and New Zealand. All four species are vectored by psyllid insects of different genera. Here, we show that the pear psyllid pest Cacopsylla pyri (L.) hosts a novel liberibacter species that we named ‘ Ca. Liberibacter europaeus’. It can bloom to high titres in the psyllid host, with more than 10 9 16S rRNA gene copies per individual. Fluorescent in situ hybridization experiments showed that ‘ Ca. L. europaeus’ is present in the host midgut lumen, salivary glands and Malpighian tubules. ‘ Candidatus L. europaeus’ has a relatively high prevalence (> 51%) in C. pyri from different areas in the Piedmont and Valle d'Aosta regions in Italy and can be transmitted to pear plants in experimental transmission trials. However, even though high titres of the bacterium (more than 10 8 16S rRNA gene copies g −1 of pear plant tissue) could be detected, in the pear tissues no specific disease symptoms could be observed in the infected plants over a 6‐month period. Despite liberibacters representing potential quarantine organisms, ‘ Ca. L. europaeus’, first described in Italy and Europe, apparently behaves as an endophyte rather than a pathogen.

Different mosquito species host Wickerhamomyces anomalus (Pichia anomala): perspectives on vector-borne diseases symbiotic control - Irene Ricci; Michela Mosca; Matteo Valzano; Claudia Damiani; Patrizia Scuppa; Paolo Rossi; Elena Crotti; Alessia Cappelli; Ulisse Ulissi; Aida Capone; Fulvio Esposito; Alberto Alma; et al. (Antonie van Leeuwenhoek, 2011)

Asaia , a versatile acetic acid bacterial symbiont, capable of cross‐colonizing insects of phylogenetically distant genera and orders - Elena Crotti; Claudia Damiani; Massimo Pajoro; Elena Gonella; Aurora Rizzi; Irene Ricci; Ilaria Negri; Patrizia Scuppa; Paolo Rossi; Patrizia Ballarini; Noura Raddadi; Massimo Marzorati; et al. (Environmental Microbiology, 2009)
Summary Bacterial symbionts of insects have been proposed for blocking transmission of vector‐borne pathogens. However, in many vector models the ecology of symbionts and their capability of cross‐colonizing different hosts, an important feature in the symbiotic control approach, is poorly known. Here we show that the acetic acid bacterium Asaia , previously found in the malaria mosquito vector Anopheles stephensi , is also present in, and capable of cross‐colonizing other sugar‐feeding insects of phylogenetically distant genera and orders. PCR, real‐time PCR and in situ hybridization experiments showed Asaia in the body of the mosquito Aedes aegypti and the leafhopper Scaphoideus titanus , vectors of human viruses and a grapevine phytoplasma respectively. Cross‐colonization patterns of the body of Ae. aegypti , An. stephensi and S. titanus have been documented with Asaia strains isolated from An. stephensi or Ae. aegypti , and labelled with plasmid‐ or chromosome‐encoded fluorescent proteins (Gfp and DsRed respectively). Fluorescence and confocal microscopy showed that Asaia , administered with the sugar meal, efficiently colonized guts, male and female reproductive systems and the salivary glands. The ability in cross‐colonizing insects of phylogenetically distant orders indicated that Asaia adopts body invasion mechanisms independent from host‐specific biological characteristics. This versatility is an important property for the development of symbiont‐based control of different vector‐borne diseases.

Composition, abundance and phytoplasma infection in the hawthorn psyllid fauna of northwestern Italy - Rosemarie Tedeschi; Pavel Lauterer; Lorenzo Brusetti; Federica Tota; Alberto Alma (European Journal of Plant Pathology, 2009)

Rearing, release and settlement prospect in Italy of Torymus sinensis, the biological control agent of the chestnut gall wasp Dryocosmus kuriphilus - Ambra Quacchia; Seiichi Moriya; Giovanni Bosio; Ivano Scapin; Alberto Alma (BioControl, 2008)

Can the Geranium Bronze, Cacyreus marshalli, become a threat for European biodiversity? - Ambra Quacchia; Chiara Ferracini; Simona Bonelli; Emilio Balletto; Alberto Alma (Biodiversity and Conservation, 2008)